Developing digital literacy application for Extensive Listening materials - Maslikah, Khotim; Widiati, Utami; Wulyani, Anik Nunuk; Tengku Sharif, Tengku Intan Suzila (Bahasa dan Seni: Jurnal Bahasa, Sastra, Seni, dan Pengajarannya, 2023)
Learning resource transformation is essential in this digital era, and English teaching and learning is no exception, especially in Madrasah context. That is why providing digital Extensive Listening (EL) materials to promote comprehensible input and character values is needed. This study outlines how Muslim English Literacy (MEL) application was developed to support the digital transformation as an alternative for EL materials. Research and Development (R & D) design was executed comprising seven phases of needs assessment, product design and development, product validation, first round of product revision, field testing, second round of product revision, and final product dissemination. The results of the field testing and moderation suggest that the developed product, MEL, is practical and applicable in helping EFL students to get more language exposure so that their English language acquisition can be facilitated. In addition, the product integrating character values may also strengthen their identity of being Muslims. Further studies on similar material development with more various topics utilizing technology apps are worth conducting.